2014
DOI: 10.1590/1516-3180.2014.1321575
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of children and adolescents with hemangioma using propranolol: preliminary results from a retrospective study

Abstract: CONTEXT AND OBJECTIVE: Hemangiomas are the commonest vascular tumors during childhood. In 2008, the effect of propranolol for treating capillary hemangiomas was demonstrated. Other similar results followed, showing that it rapidly reduces lesion volume. The objective here was to evaluate children and adolescents with hemangiomas that were treated with propranolol. DESIGN AND SETTING: Retrospective study, conducted in a children's hospital. METHODS: Patients aged 0-19 years with or without previous treatment, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…In a study with two groups of patients, 37 out of 38 patients showed response to propranolol who started treatment before reaching the age of one year (97%), whereas the proportion was 23 out of 31 patients who started treatment after reaching one year of age (74%). 21 Our patient population was all in the proliferative stage or near its end. The previous study could suggest that propranolol could be a valuable medical treatment for cases presented late after the end of the proliferative stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study with two groups of patients, 37 out of 38 patients showed response to propranolol who started treatment before reaching the age of one year (97%), whereas the proportion was 23 out of 31 patients who started treatment after reaching one year of age (74%). 21 Our patient population was all in the proliferative stage or near its end. The previous study could suggest that propranolol could be a valuable medical treatment for cases presented late after the end of the proliferative stage.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Slowly increasing the dose of the drug and close monitoring of heart rate, blood pressure, and serum glucose levels have also been recommended in the initial phase of treatment. 27,28 Albuquerque et al 21 reported their results with 69 patients with hemangiomas treated with propranolol. They reported no cases needed to discontinue propranolol due to serious or intolerable side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posteriormente, segue-se um período de estabilidade ou platô, que persiste por alguns meses, culminando em uma fase de involução lenta, que se inicia, em geral, entre 12 e 18 meses de vida. 1,3,[5][6][7] Estima-se que a involução completa ocorra ao ritmo de 10% ao ano, 2 e lesões remanescentes após o 6º ano de vida cursam com alterações residuais, como telangiesctasias, atrofias, cicatrizes e áreas de alopecia. 5 O diagnóstico, na maioria dos casos, é clínico.…”
Section: Descrição Do Casounclassified
“…35 In contrast to corticosteroids, propranolol is effective in treating hemangiomas in children of all ages, and not limited to the proliferative stage of the lesions. 36 The recommended dose is 1 to 3 mg/kg/day divided in three doses. 37 Clinical improvement is evident in the majority of patients within the first week of treatment.…”
Section: Managementmentioning
confidence: 99%